KEHARMONISAN RUMAH TANGGA PADA PASANGAN DIBAWAH UMUR DIDESA KEMANTREN KECAMATAN JABUNG KABUPATEN MALANG - Nun Maulana Khaidir Al Muzli; Ahmad Subekti; Rosichin Mansur (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Marriage is a bond between a man and a woman as a husband and wife to create an eternal and happy family based on teachings of islam. Therefore marriage has some requirements that must be met oe has an age limit that's 16 years for women and 19 years for men. But the fact is that underage marriage phenomena are still very common in kemantren village,jabung sub district,malang municipility.This study was intended to find out just how great the harmony of the household was. It's a kind of descriptive qualitative research using methods of in-depth interviews on subjects that were then analyzed for research results. Studies indicate that according to religious figures in kemantren village,jabung sub-district,malang municipility that the couples under age are mostly harmonious,sometimes quarrels happen but can be resolved well. According to other underage couples also provide information that their families are harmonious,Even though sometimes they fight. Some of the arguments are due to economic factors and their children. But those minors put their families ahead of their own interests.Keyword : harmony of the household, early marriage, underage marriage.